INSULIN AUTOIMMUNE SYNDROME OR INSULINOMA? UNRAVELLING THE CAUSE OF HYPERINSULINEMIC HYPOGLYCEMIA IN A PATIENT WITH A PANCREATIC CYST - Tan, Ying-Jie; Eng, Shinye; Khoo, Jun-Kit; Ratnasingam, Jeyakantha; Lim, Lee-Ling; Vethakkan, SR (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Insulin Autoimmune Syndrome (IAS) constitutes a rare aetiology of non-diabetic endogenous hyperinsulinemic hypoglycaemia, with a prevalence of 4.9–11.7%. We report a case of a 61-year-old Chinese female who was confirmed to have endogenous hyperinsulinemic hypoglycaemia. Subsequent imaging revealed a cystic pancreatic lesion, while insulin autoimmune antibodies (IAA) were mildly elevated. This case highlights the challenge of distinguishing between insulinoma and IAS. CASE A 61-year-old Chinese female, with no prior diabetes, presented in April 2024 with symptoms suggestive of Whipple’s triad. She experienced both fasting and post-prandial hypoglycemia (2.0–3.0 mmol/L) and postprandial hyperglycemia (up to 16 mmol/L). She had no significant drug history except recent glucosamine use two weeks prior. A 72-hour fasting test confirmed endogenous hyperinsulinemia with elevated insulin (245 U/mL) and C-peptide (13.3 ng/mL) at a plasma glucose of 2.6 mmol/L, with a molar insulin-to-C-peptide ratio of 0.4. Sulfonylurea screening was negative, but IAA was mildly elevated at 17.9 U/mL (<2.4). Pancreatic CT scan revealed a 9 mm non-enhancing hypodense lesion in the pancreatic body, and endoscopic evaluation found a 7 × 5 mm pancreatic cyst. Ga68 DOTATATE PET-CT showed no uptake, and arterial stimulation venous sampling (ASVS) was negative for insulinoma or nesidioblastosis. PEG precipitation of random insulin indicated low insulin recovery (7.5%), confirming IAA interference. She was started on diazoxide and a low-glycemic diet with small frequent meals. Her hypoglycaemia spontaneously resolved within three months, even after stopping diazoxide prior to ASVS. Given the negative ASVS, positive IAA, and spontaneous resolution, IAS was diagnosed. She was commenced on acarbose 50 mg TDS and remains well, with continuous glucose monitoring showing infrequent hypoglycemia and milder postprandial hyperglycemia. CONCLUSION This case underscores the diagnostic complexity of differentiating IAS from cystic insulinoma in a patient with endogenous hyperinsulinemic hypoglycemia, a cystic pancreatic lesion, and elevated IAA.